Apoptosis and Efferocytosis in Inflammatory Diseases - Chandra Agung Purnama; Anna Meiliana; Melisa Intan Barliana; Keri Lestari Dandan; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Millions of cells in multicellular organisms regenerate every day to replace aged and died cells. Effective cell clearance (efferocytosis) is critical for tissue homeostasis, as the human body recycles its cellular components. We summarize what is known about the mechanisms of efferocytosis and how it impacts the physiology of the organism, effects on inflammation and the adaptive immune response, as well as the consequences of defects in this critical homeostatic mechanism in this review.CONTENT: Cell death is the process by which the human body replaces aged or damaged cells with new ones. It can be triggered by genetically encoded machinery or regulated cell death, or by specific pharmacologic or genetic interventions, resulting in accidental cell death. Dying cells release signals that entice phagocytes to engulf them in a process known as efferocytosis. Efferocytosis is a multistep process involving the release of “find me” and “eat me” signals and destruction of death cells by phagocytes. Different types of cell death including apoptosis and necroptosis can express pro- or anti-inflammatory signals via macrophage activity modulation.SUMMARY: Failed or ineffective efferocytosis can result in disruption of tissue homeostasis, which can contribute to the development of chronic inflammatory diseases such as atherosclerosis, obesity, diabetes, and heart failure. Therefore, any therapeutic strategy that enhances efferocytosis will have a beneficial effect on the treatment of these metabolic disorders.KEYWORDS: apoptosis, necroptosis, phagocytosis, efferocytosis, macrophage.